A boy with 13.34-Mb interstitial deletion of chromosome 4p15: A new case report and review of the literature. Issue 51 (December 2017) - Mitroi, Anca Florentina; Aschie, Mariana; Apostol, Adriana; Brinzan, Costel; Cozaru, Georgeta; Mitroi, Adrian Nelutu
Abstract: Rationale: To date, >40 cases have been described with interstitial deletions involving the 4p15 region. Patient concerns and diagnosis: We report a case of a 3-year-old boy with an interstitial de novo deletion of approximately 13.34 Mb in 4p15.1–15.31 having mild developmental delay and multiple minor congenital abnormalities. Lessons: This case presents a clinical manifestation that is similar but not identical to other reported cases. In this report, we have provided a detailed description of a 3-year-old patient with an interstitial 4p deletion and mildly affected phenotype. We discuss the possible involvement of SLIT2, KCNIP4, and LGI2 in cortical development and RBPJ in skeletal abnormalities.